2012
DOI: 10.1007/s10856-012-4695-2
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and biodegradation studies of PCL/β-TCP bone tissue scaffold fabricated by structural porogen method

Abstract: Three-dimensional printer (3DP) (Z-Corp) is a solid freeform fabrication system capable of generating sub-millimeter physical features required for tissue engineering scaffolds. By using plaster composite materials, 3DP can fabricate a universal porogen which can be injected with a wide range of high melting temperature biomaterials. Here we report results toward the manufacture of either pure polycaprolactone (PCL) or homogeneous composites of 90/10 or 80/20 (w/w) PCL/beta-tricalcium phosphate (β-TCP) by inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…Ang et al [64] found increased degradation of PCL-HAp composites with increasing mass loss at higher HAp contents in an accelerated degradation using NaOH 5M, although the mechanism of this degradation assay may hardly be relevant to explain our results. In most studies very short times are used (from 7 days to 6 weeks) and the weight losses observed are mainly due to inorganic phase dissolution (when using TCP, see for example Lu et al [65] or HAp in thin PCL layer Kim el al. [66]) as physical degradation of PCL is known to occur on a much larger timescale.…”
Section: Influence Of Hap Reinforcement On Weight Loss and Molecular mentioning
confidence: 99%
“…Ang et al [64] found increased degradation of PCL-HAp composites with increasing mass loss at higher HAp contents in an accelerated degradation using NaOH 5M, although the mechanism of this degradation assay may hardly be relevant to explain our results. In most studies very short times are used (from 7 days to 6 weeks) and the weight losses observed are mainly due to inorganic phase dissolution (when using TCP, see for example Lu et al [65] or HAp in thin PCL layer Kim el al. [66]) as physical degradation of PCL is known to occur on a much larger timescale.…”
Section: Influence Of Hap Reinforcement On Weight Loss and Molecular mentioning
confidence: 99%
“…Ternary blends tested; PCL/PGA/TCP blends (80/10/10 and 70/10/20) retained the adhesive strength of the parent PCL adhesive while having an improvement in hydrophilicity. Porous PCL scaffolds containing 20% TCP have been described as degrading faster than PCL alone, while supporting osteoblast growth …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the processes are performed at room temperature, heat-sensitive biologically active factors can be added during printing (Chia and Wu, 2015). However, the final products usually have weak biomechanical strength, which require high-temperature sintering to obtain structures suitable for bone tissue engineering (Seitz et al, 2005;Lu et al, 2012;Tarafder et al, 2013;Tarafder and Bose, 2014;Qian et al, 2015). Exploration of better binders is currently underway (Inzana et al, 2014).…”
Section: D Printingmentioning
confidence: 99%